Analisis Pengaruh Intensitas Penggunaan Aplikasi Tiktok terhadap Prokrastinasi Akademik Mahasiswa: A Theory of Planned Behavior Perspective - Az Zahro Ubaidillah Anufi; Bernadetta Pakpahan; Nayla Agustina Nuraini; Rhefangga Dwi Fa’asza; Veisha Alya Aisyah; Joko Tri Nugraha (AKADEMIK: Jurnal Mahasiswa Humanis, 2026)
The rapid growth of TikTok usage among university students raises concerns about its potential impact on academic behavior, particularly academic procrastination. This study aims to examine the effect of TikTok usage intensity on academic procrastination from the perspective of the Theory of Planned Behavior (TPB). A quantitative survey method was employed involving 90 undergraduate students from the Public Administration program at Universitas Tidar, selected using purposive sampling. Data were collected through a structured questionnaire based on TPB constructs (attitude, subjective norms, and perceived behavioral control) and academic procrastination indicators, measured using a five-point Likert scale. The data were analyzed using multiple linear regression with SPSS. The results indicate that, partially, attitude and subjective norms do not have a significant effect on academic procrastination. In contrast, perceived behavioral control has a significant negative effect, indicating that higher self-control is associated with lower levels of procrastination. Simultaneously, all TPB variables significantly influence academic procrastination, although the explanatory power is relatively low (Adjusted R² = 0.128). These findings highlight the importance of self-regulation in managing social media use among students.